2019
DOI: 10.1161/jaha.119.012093
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Amlodipine in Early Pregnancy

Abstract: BackgroundAmlodipine is used for the treatment of hypertension, but reports on its use in early pregnancy are limited.Methods and ResultsIn the present study, we recruited 231 women with chronic hypertension, including those who received amlodipine or other antihypertensives during early pregnancy, and investigated frequencies of morphologic abnormalities in their 231 offspring. Specifically, we evaluated 48 neonates exposed to amlodipine in the first trimester (amlodipine group, Group A), 54 neonates exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…Previous studies have demonstrated that the occurrence of preeclampsia was tightly linked with the decreased bioavailability of VEGF [ 53 55 ]. Moreover, results of our study and others [ 56 , 57 ] have also showed that the preeclamptic symptom could be relieved after the treatment of Aml. Additionally, in the vascular endothelium of the thyroid gland and liver, VEGF has been found to be highly expressed; the suppression of VEGF cellular signaling pathways can result in vascular disturbances and even regression in these organs [ 58 60 ].…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have demonstrated that the occurrence of preeclampsia was tightly linked with the decreased bioavailability of VEGF [ 53 55 ]. Moreover, results of our study and others [ 56 , 57 ] have also showed that the preeclamptic symptom could be relieved after the treatment of Aml. Additionally, in the vascular endothelium of the thyroid gland and liver, VEGF has been found to be highly expressed; the suppression of VEGF cellular signaling pathways can result in vascular disturbances and even regression in these organs [ 58 60 ].…”
Section: Discussionsupporting
confidence: 77%
“…2,14,158,184,185 Small clinical trials and observational studies suggest that amlodipine, clonidine, and thiazide diuretics are probably safe in pregnancy as well. 177,186,187 It is also widely accepted that all renin-angiotensin system blockers should be avoided during pregnancy, 188 especially during the second and third trimesters when blockade of the fetal renin-angiotensin system clearly interferes with kidney development and function. Given suboptimal and frequently contradicting data on fetal safety after exposure to antihypertensive medications in utero, well-designed, carefully controlled trials are needed, with attention given to short- and long-term fetal and maternal outcomes.…”
Section: Treatment Of Hypertension In Pregnancymentioning
confidence: 99%
“…23,24 In yet another retrospective study of birth outcomes of 231 pregnant women with hypertension, the authors concluded that amlodipine did not appear to be associated with increased rate of foetal malformations compared with other anti-hypertensive medications or maternal hypertension without any drug treatment. 25 Similarly, a pharmacoepidemiological study did not find any increase in the risk of congenital anomalies due to CCBs given during pregnancy. 26 A multicenter prospective observational study of the European Network of Teratology Information Services and other studies have found little association between congenital malformations and CCBs use in early pregnancy.…”
Section: Discussionmentioning
confidence: 94%